TOWARDS A NEW ERA OF LANGUAGE LEARNING: PREDICTING TRENDS AND CHALLENGES OF AI INTEGRATION IN THE FUTURE - Madjid, Abd. (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
The rapid advancements in Artificial Intelligence (AI) technology have significantly transformed the landscape of language learning. This paper explores the integration of AI-driven tools, such as intelligent tutoring systems and chatbots, in providing personalized learning experiences and tailored feedback that cater to individual learner preferences. The study employs a descriptive qualitative approach, reviewing existing literature to assess both the potential benefits and challenges posed by AI in language education. Key findings reveal that while AI can enhance engagement and learning outcomes, it also raises important ethical concerns related to data privacy and the necessity for adequate teacher training. The conclusions emphasize the need for a balanced and ethical approach in adopting AI technologies to ensure they effectively support both educators and learners in the evolving educational environment.